A secure coverage area expansion scheme for public wireless LAN services. (1st October 2010) - Watanabe, Ryu; Tanaka, Toshiaki
An ad-hoc network style connection can be utilised to expand the coverage area of public wireless LAN (WLAN) services. By relaying the messages among user nodes, a node can obtain an internet connection, even though the node is located outside the AP's direct wireless communication area. This concept has been realised by using the ad-hoc on-demand distance vector (AODV) routing protocol and mobile IP. However, it has some drawbacks in terms of security. The AODV has no functions for confirming the validity of routing messages; therefore, there are many threats due to faked or forged routing messages. In contrast, if a secure ad-hoc routing protocol is used for message routing in the WLAN service, the message route can be appropriately maintained. However, in order to employ secure ad-hoc routing protocols, a key and IP address have to be securely delivered to each WLAN node in advance. For this purpose, in this paper, the authors propose a secure address and public key certificate allocation scheme for WLAN services.